Nigeria: Impacts of the Ukraine and Global Crisis on Food Systems and Poverty - Andam, Kwaw S.; Diao, Xinshen; Dorosh, Paul; Pradesha, Angga; Thurlow, James (2022)
Presentation prepared by Kwaw Andam, Xinshen Diao, Paul Dorosh, Angga Pradesha, and James Thurlow, all with the International Food Policy Research Institute, Washington DC. This is part of the Global Crisis Series.